Current Advances in Pharmacotherapy and Technology for Diabetic Retinopathy: A Systematic Review - Lei Lu; Ying Jiang; Ravindran Jaganathan; Yanli Hao (Journal of Ophthalmology)
Diabetic retinopathy (DR) is classically defined by its vascular lesions and damage in the neurons of the retina. The cellular and clinical elements of DR have many features of chronic inflammation. Understanding the individual cell-specific inflammatory changes in the retina may lead to novel therapeutic approaches to prevent vision loss. The systematic use of available pharmacotherapy has been reported as a useful adjunct tool to laser photocoagulation, a gold standard therapy for DR. Direct injections or intravitreal anti-inflammatory and antiangiogenesis agents are widely used pharmacotherapy to effectively treat DR and diabetic macular edema (DME). However, their effectiveness is short term, and the delivery system is often associated with adverse effects, such as cataract and increased intraocular pressure. Further, systemic agents (particularly hypoglycemic, hypolipidemic, and antihypertensive agents) and plants-based drugs have also provided promising treatment in the progression of DR. Recently, advancements in pluripotent stem cells technology enable restoration of retinal functionalities after transplantation of these cells into animals with retinal degeneration. This review paper summarizes the developments in the current and potential pharmacotherapy and therapeutic technology of DR. Literature search was done on online databases, PubMed, Google Scholar, clinitrials.gov, and browsing through individual ophthalmology journals and leading pharmaceutical company websites.